Mind, body, and the philosophical theology of Donald M. MacKay - Norman, David A. (The University of Edinburgh, 2004)
In this thesis, we are seeking to examine a relatively narrow aspect of the work of Donald M. MacKay. In particular, we are seeking to examine his work in relation to a very specific problem as it presents itself to a relatively specific group of people. The problem we will seek MacKay's help in working through is what has come to be known by contemporary Anglo/American philosophers as 'the mind/body problem'. The group of people we will be attempting to help deal with this problem is the contemporary evangelical Christian Church.

What we are dealing with is essentially a contemporary problem as it relates to a contemporary system of belief. Though in this sense, this thesis is decidedly not historical, it must be acknowledged that the historical roots of both the system of belief it sets out to preserve and the problem it sets out to work through run very deeply. In fact, even before God's people were called 'the Christian Church', there was a mind/body problem—and ever since the Church took up the task of explaining her beliefs, something like the mind/body problem has been an issue.

After introducing the mind/body problem as it relates to the contemporary evangelical Christian Church in chapter 1 and the career of Donald MacKay as it relates to the mind/body problem in chapter 2, we proceeded to explain MacKay's metaphysical anthropology.

The key to understanding MacKay's metaphysical anthropology is his understanding of logical complementarity. Accordingly, we devoted chapter 3 to the task of expositing his work in that area before proceeding, in chapter 4, to explain in more detail how this understanding related to the mind/body problem. We saw in chapter 4 that MacKay's understanding of logical complementarity allowed him to say that human beings are multi-faceted creatures—creatures that may be meaningfully described in many different kinds of ways. Most significantly, MacKay argued that although mental descriptions and physical descriptions necessitate radically different standpoints, they do not necessitate substantially different subjects.

In saying that mental descriptions and physical descriptions can apply to human beings with equal validity, however, he raised the following objections from other evangelicals: 1) If physical descriptions really apply to me in the same way that mental descriptions do, and the subjects ofphysical descriptions must always obey the mechanical laws of cause and effect, how can /be said to befree? And 2) If mental descriptions and physical descriptions really apply to the same 'me', how can I reasonably hope for mental life after my body dies?

Since MacKay dealt with this first objection rather extensively and consistently throughout his academic life, Chapter 5 was devoted to explaining and evaluating his response.

With regard to the second objection, however, MacKay seems to have altered his position somewhat in the final years of his career. Since this alteration in his position may have been at least partly due to the complexity ofrelated theological issues, we spent the first half of chapter 6 explaining these complex issues by investigating the related controversies in biblical, philosophical, and systematic Mind, Body, and the Philosophical Theology of Donald M. MacKay theology during MacKay's lifetime. In the second half of chapter 6, we explained the shift in MacKay's position relative to this second objection as it relates to these theological controversies.